Why Has Science Become an Old Man's Game? - Christian Fons-Rosen; Patrick Gaule; Taras Hrendash (Institute of Labor Economics (IZA), 2023)
We investigate the causes and consequences of the aging of the scientific workforce. Using novel data on the population of US chemistry faculty members over fifty years, we find that the secular increase in the age of the academic workforce has been mainly driven by the slowdown in faculty hiring combined with later retirements. By contrast, changes in the age at which scientists start their careers only contribute to about 20% of aging. Hiring more new faculty members could rejuvenate the scientific workforce and boost scientific productivity.
Keywords: O31; J24; J26; 330; aging; science; universities; knowledge production